Intercultural Responses To Korean Drama Series On Part Of University Students In Indonesia - Briandana, Rizki (2015)
At the end of 1990s, the increasing number of Korean cultural products (K-Pop), including television dramas, movies and songs have gained popularity in the East and Southeast Asian region. In addition to that, the Asian economic crisis in the 1990s led to a situation in which had marked an influence on Asian buyers to consume Korean cultural products. In Indonesia, Korean drama series gain a promising reception from a huge number of fans. This is shown by the increasing number of Korean dramas being shown on various television stations in Indonesia. This study is based on the framework of reception theory, that specifically suggests that the audience are the active media texts interpreter. This theory opens up a broader conception of what audiences might do with texts, in order to allow for the ritual uses of communications as well as the transmission of media contents from producers to the audience. As a result of two methods that are used in this research which are textual analysis and focus group discussion. The analysis of this research shows that social values of materialism, patriarchy, and class differences are prominent in the series like Princess Hours and Secret Garden. The leading male characters are portrayed as proud and selfish. Resembling the typical characteristic of soap opera genre, most Korean dramas will end in a constructive way where the protagonist eventually changes and adapts the positive values. The respondents who are involved in this research seem to enjoy watching Princess Hours and Secret Garden because of the diversified ways of connecting to the audience’s emotion by portraying attractive protagonists, compelling theme songs and dramatic storylines. The findings support Ien Ang’s (1985) ‘melodramatic realism’ by looking at the position of explaining the emotional realism of tragic structure of feeling, which is represented in the drama – which in the case of Korean dramas, is translated through the rise and fall of the story with the depiction of excessive emotion and deep feeling.